Effects of injection strategy and combustion chamber modification on a single-cylinder diesel engine - GÜL, MEHMET ZAFER; YANGAZ, MURAT UMUT; ŞENER, RAMAZAN (ELSEVIER SCI LTD, 2020)
The diesel engine is widely used due to its thermal efficiency, reliability and fuel economy, while diesel engine emissions are harmful to the environment and human health. Therefore, the standards (EPA, Tier, NRE-v/c standards, etc.) limit the exhaust emission of engines around the world. The most successful method of reducing emissions is to optimize the combustion chamber and the fluid motion inside the engine. In this study, experimental and numerical methods were used in a diesel engine to analyze fluid motion, spray, combustion process, and exhaust emissions. A new type of swirl piston bowls and a reentrant piston bowl were utilized on a baseline diesel engine. Different spray angles and injection pressures were applied and results were compared with the baseline design. Results show that the piston bowl shape has a critical influence on engine performance and emissions. Since the multi-swirl piston bowl (MSB) and double-swirl piston bowl (DSB) design increases in-cylinder swirl and turbulence, it contributes to reducing emissions and improving the combustion process. Increasing spray angle and injection pressure and using of DSB can reduce the soot emissions by 81%. DSB and MSB improve the combustion process but also increase NOx emissions due to increased in-cylinder temperature. On the other hand, NOx emissions may also be reduced if the injection parameters of the engine are optimized to provide the same power with the new swirl bowls.
Keywords: Diesel engine; Fuel; Combustion; Emission; CFD; Swirl bowl; PISTON BOWL GEOMETRY; EMISSIONS CHARACTERISTICS; HEAT-TRANSFER; OPTIMIZATION; SYSTEM; MECHANISMS; GASOLINE; MODEL; FLOW